KENAIKAN ANGGARAN MILITER DALAM KONTEKS KEMANUSIAAN MODERN FACE IN HUMANITARIAN WORLD - Rifqi Itsnaini Yusuf (CV. Amerta Media, 2019)
This article aims to analyze the development of the increase in the country's military budget in the context of humanity and see it in a modern face of humanitarian world perspective. This article argues that there is a significant influence from the increase in the state's military budget on existing humanitarian issues. The increase in a country's military budget has at least two impacts, namely domestic and international impacts. Improving regional security and stability in the domestic context is one of the effects of an increase in a country's military budget. neighboring countries concerns over an increase in a country's budget reflects the adverse impact of the increase in the budget. The existence of these concerns will actually raise the tension of relations between countries that are in conflict. The conflict resulting from the increase in tension that is built will threaten existing humanitarian aspectsKey Words: Military, State, Humanitarian, Stability, Security.